2019
DOI: 10.1155/2019/1502963
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Management of Septic Shock among Children Admitted at the Kenyatta National Hospital, Longitudinal Survey

Abstract: Background. Paediatric septic shock is a subset of sepsis associated with high mortality. Implementing the existing international Surviving Sepsis Campaign Guidelines 2012 (SSCG) have contributed to reduction of mortality in many places but these have not been adopted in our setting. The current study aimed at documenting the practice at a national referral hospital. Methods. A hospital based longitudinal survey carried out among 325 children from September to October 2016. Children aged 0 days (≥37 weeks gest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 30 publications
(30 reference statements)
3
14
0
4
Order By: Relevance
“…In contrast, Vekaria-Hirani et al . [ 10 ] in Kenya found that septic shock was commoner in the younger age groups with infants having the highest case fatality rates, apparently due to a majority of their participants being infants, including neonates. Moreover, the duration of the illnesses before admission in CHER as well as gender was not significantly associated with shock in this study; this may be due to the overall shortness of disease duration among our participants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, Vekaria-Hirani et al . [ 10 ] in Kenya found that septic shock was commoner in the younger age groups with infants having the highest case fatality rates, apparently due to a majority of their participants being infants, including neonates. Moreover, the duration of the illnesses before admission in CHER as well as gender was not significantly associated with shock in this study; this may be due to the overall shortness of disease duration among our participants.…”
Section: Discussionmentioning
confidence: 99%
“…The quality of care and referral threshold of referring hospitals as well as the expertise of transport team can influence the severity of illness at presentation in a tertiary centre [ 10 , 25 ]. In this index study, the source of referral was significantly associated with the presence of shock at presentation; children arriving from private clinic were twice more likely to present with circulatory failure in CHER.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maitland et al reported an increase in mortality after fluids bolus in African children with severe infection (44). Studies by Kortz et al (Tanzania) and Vekaria-Hirani et al (Naroby) did not observe reduction on mortality after a protocol implementation (34,45). Kortz et al even observed an increase in length of stay after protocol implementation caused by complications of treatment (34).…”
Section: Challenges In Low-middle-income Countriesmentioning
confidence: 99%
“…Os autores do estudo discutiram que os fatores que poderiam estar associados ao óbito precoce seriam: indisponibilidade de leitos de UTI, atraso no reconhecimento e tratamento, falta de atenção às diretrizes e dificuldade de transferência para serviço terciário. 19 O fato de que os pacientes apresentavam à admissão várias disfunções orgânicas pode refletir uma chegada tardia ao hospital. Launay et al…”
Section: Mortalidadeunclassified